Motivasi Wisatawan Domestik Dan Pengaruhnya Terhadap Keputusan Berkunjung Ke Daya Tarik Wisata Pantai Pandawa: Motivasi Wisatawan Domestik Dan Pengaruhnya Terhadap Keputusan Berkunjung Ke Daya Tarik Wisata Pantai Pandawa - Anjeli Wahyuningtyas, Ni Wayan; Wiarti, Luh Yusni; Winarya, I Wayan Sukma (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Tourist motivation is a factor that influences tourists in determining the decision to visit a tourist attraction. Therefore, understanding what motivates tourists is very important in improving the tourism industry to become quality and superior tourism. This research was conducted at Pandawa Beach which aims to find out what tourist motivations underlie tourists to visit, and to find out the effect of partial and simultaneous tourist motivation on the decision for visiting Pandawa Beach Tourist Attraction. This research uses a quantitative approach with multiple linear regression analysis methods through the SPSS 24 software program. This survey used 100 domestic tourist respondents. The result of this study is that the dominant tourist motivation underlying tourists visiting Pandawa Beach is social motivation with a score of 4.57. Meanwhile, from the partial effect of tourist motivation on visiting decisions, namely all dimensions of tourist motivation have a positive effect on visiting decisions. Overall or simultaneously tourist motivation affects visiting decisions, the value of Fcount is 113.213. The conclusion is that 82.7% of the visiting decision variable is affected by the tourist motivation variable, while 17.3% is influenced by the other variables outside of this research.